Desempenho da Atenção Primária à Saúde no controle da hanseníase em Minas Gerais - Daniele dos Santos Lages (2022)
Leprosy is a public health problem in Brazil due to its magnitude and transcendence. Therefore, decentralized Leprosy Control Actions (LCA) were established. Thus, understanding the trend and the relationship of epidemiological and operational indicators of leprosy with the level of decentralization of LCA to Primary Health Care (PHC) allows us to know if there was an impact on the performance of this level of care, and on its coverage for leprosy control in Minas Gerais (MG). The objective was to analyze the performance of PHC in leprosy control in Minas Gerais. This is an observational and analytical epidemiological study of the ecological type, of time series, in the state of MG and in its macro and micro health regions. The study population was composed of new cases of leprosy reported by the Sistema de Informação de Agravos de Notificação (SINAN), residents in MG, from 2001 to 2020. The data were made available by the State Leprosy Coordination of MG. The outcome of the study was the decentralization of LCA. The explanatory variables were those dealing with the performance of primary care and the epidemiological situation. For the trend analyses, Prais-Winsten linear regression was performed, using the Antunes and Cardoso method. The software used in the study were Stata (version 14.0), IBM SPSS Statistics 19, and Microsoft Excel (Virtual Basic for Applications). The study is part of the project entitled "Epidemiological analysis of leprosy in the state of Minas Gerais", developed by the Núcleo de Estudos e Pesquisas em Hanseníase (NEPHANS) of the Escola de Enfermagem da Universidade Federal de Minas Gerais (UFMG), and approved by the Ethics Committee for Research with Human Beings (COEP) of UFMG, under opinion no.: 490.456, CEP UFMG - CAAE 248993137.0000.5149. The study reveals that, in Minas Gerais, during the period studied, 37041 new cases of leprosy were reported, with an average of 1852 annual diagnoses throughout the state territory, establishing a medium endemicity of the disease. In the state there is not only the expansion of the coverage of Basic Care and Family Health Strategy, but also a movement of decentralization of LCA to PHC and that a large part of the epidemiological and operational indicators developed favorably as the decentralization of LCA occurred, i.e, However, when analyzing the entire state and also its macro and microregions of health in an isolated way, one notices suggestive signs of the presence of a hidden endemic in several regions of the state, a factor that contributes to the perpetuation of the leprosy transmission chain. Therefore, the different results found in micro and macro health regions demand further studies, aiming not only at understanding the leprosy surveillance and control actions but also the socioeconomic factors that characterize that population.